2000
DOI: 10.1097/00006454-200006000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-acquired adenovirus 7h infantile respiratory infection in Chile

Abstract: The high secondary attack rate observed, stresses the importance of adequate isolation of patients and the need for rapid and sensitive viral diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0
13

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 9 publications
2
27
0
13
Order By: Relevance
“…Respiratory syncytial virus (RSV) is the principal cause of ALRI, causing yearly winter epidemics that frequently challenge health resources (3,4,5,9,12,15,21). The expanded use of new techniques has facilitated the local identification of etiologic agents, allowing the comparison of clinical and epidemiological features with biological agent characteristics (2,6,7,14,16,17,19). The aim of this study is to present an overview of RSV infection causing pediatric admissions for ALRI in Chile over a long enough period of time to support recommendations for better clinical and epidemiological management.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Respiratory syncytial virus (RSV) is the principal cause of ALRI, causing yearly winter epidemics that frequently challenge health resources (3,4,5,9,12,15,21). The expanded use of new techniques has facilitated the local identification of etiologic agents, allowing the comparison of clinical and epidemiological features with biological agent characteristics (2,6,7,14,16,17,19). The aim of this study is to present an overview of RSV infection causing pediatric admissions for ALRI in Chile over a long enough period of time to support recommendations for better clinical and epidemiological management.…”
mentioning
confidence: 99%
“…Confirmatory IFA for RSV, adenovirus, influenza A and B viruses, and parainfluenza viruses 1 to 3 were performed for cultures with and without CPE. Standard IFA was done using monoclonal antibodies provided by L. Anderson, Centers for Disease Control and Prevention (CDC), Atlanta, Ga., and P. Pothier, Dijon, France, as previously described (3,17). From 1994 to 2000, RSV strains from NPA or positive cultures were grouped by IFA with monoclonal antibodies 133-1H and 93-11C (CDC) and 2B8 (P. Pothier) for group A typing and 102-10B (CDC) for group B typing (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hospitalised patients presenting haematological diseases, with prolonged hospital stays, are at a high risk of severe HAdV infection and represent a potential source of nosocomial outbreaks 25 . Studies have reported rates of HAdV infection ranging from 2 to 21%, with a mortality rate of 10-60%, depending on the immunosuppressive regimen used 26 .…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…48 En este sentido son factores de riesgo: edad menor de 12 meses, antecedente de hospitalización reciente por infección del tracto respiratorio inferior, inmunodeficiencia subyacente, antecedentes de neumonía o asma e infección nosocomial por adenovirus. 49,50 En países endémi-cos también destacan las micobacterias (M. tuber-culosis y micobacterias atípicas). 29 Es importante tener presente la bronquitis bacteriana persistente como causa de bronquiectasias.…”
Section: Inmunodeficienciasunclassified